2002
DOI: 10.1590/s0021-75572002000800010
|View full text |Cite
|
Sign up to set email alerts
|

Vacinas e o trato respiratório: o que devemos saber?

Abstract: ResumoObjetivo: o presente artigo tem por objetivo apresentar uma revisão acerca das principais vacinas utilizadas na população pediá-trica, com impacto direto na prevenção dos processos infecciosos infantis do trato respiratório. Fontes dos dados:foram analisadas informações de artigos publicados em revistas científicas nacionais e internacionais, selecionados por busca direta ou por pesquisa nas bases de dados Lilacs e Medline.Síntese dos dados: o artigo foi estruturado em tópicos, apresentando questões rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Furthermore, the slightly higher incidence of RSV infections in males that we found (52.6%) had also been reported previously [7,8,14,15]. RSV has been referred to as the main agent responsible for severe symptoms, such as bronchiolitis and pneumonia [2,4,13], especially during the first year of life [8,10,12,16]. In our study, 54% of the children that tested positive for RSV had bronchiolitis and pneumonia and 90% were younger than one year old, suggesting that illnesses caused by RSV might be severe for these children and thus require a fast and effective medical intervention.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, the slightly higher incidence of RSV infections in males that we found (52.6%) had also been reported previously [7,8,14,15]. RSV has been referred to as the main agent responsible for severe symptoms, such as bronchiolitis and pneumonia [2,4,13], especially during the first year of life [8,10,12,16]. In our study, 54% of the children that tested positive for RSV had bronchiolitis and pneumonia and 90% were younger than one year old, suggesting that illnesses caused by RSV might be severe for these children and thus require a fast and effective medical intervention.…”
Section: Discussionsupporting
confidence: 86%
“…It has been suggested that upon completion of the second year of life RSV has infected virtually all children at least once and 10-20% of them would have been reinfected [9]. Moreover, in the United States, RSV is responsible for 1% child hospitalization, 70% of which during the first year of life [10]. In São Paulo state, www.bjid.com.br from 1979 to 1993, respiratory infections were responsible for 18.4% of deaths in children younger than five years old [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation